Surface engineered bimetallic nanoparticles based therapeutic and imaging platform: recent advancements and future perspective. Issue 16 (1st November 2020) - Kotha, Rohini; Fernandes, Gasper; Nikam, Ajinkya Nitin; Kulkarni, Sanjay; Pandey, Abhijeet; Pandey, Sureshwar; Mutalik, Srinivas
Abstract : The unique physical and chemical properties of monometallic nanoparticles have been comprehensively explored. Analogously, the combination of two metals induces alterations in the system's electron density, termed as Bimetallic nanoparticles (BMNP's) were found to be more desirable than monometallic nanoparticles due to improved stability, activity, and selectivity, thus altering the chemical, optical, and electrical properties. In this review, we showcase the importance in the context of biomedical applications. The article sheds light on utilising BMNP's in the field of theranostics, diagnosis, and therapeutics by focusing on anticancer, antimicrobial and wound healing activity along with the toxicological problems associated with BMNP's. In conclusion, BMNP's can be used as a novel therapeutic and diagnostic system to tackle major health concerns. GRAPHICAL ABSTRACT: